Comparison of Aâ‚„ neutrino mass models - Barry, James Munnik Hamilton (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2010)
The present neutrino oscillation data are compatible with tri-bimaximal mixing, to leading order. The addition of an Aâ‚„ family symmetry and extended Higgs sector to the Standard Model can generate this mixing pattern, assuming the correct vacuum expectation value alignment of Higgs scalars. The effect of deviating this alignment is studied, for different types of Aâ‚„ models, with a phenomenological emphasis: the effect of perturbations on the model predictions for the neutrino oscillation and neutrino mass observables. The standard theoretical description of neutrino oscillations is presented, along with a summary of the past, present and future experimental efforts aimed at measuring the neutrino mixing parameters. Additionally, the current constraints on the sum of absolute neutrino masses and the amplitude for neutrinoless double beta decay, which is yet to be observed, are discussed. These constraints provide a model-independent test of family symmetery models. The Standard Model is reviewed, and extensions to the Standard Model such as the seesaw mechanism(s) are discussed: these are designed to endow neutrinos with mass, and can be incorporated into Aâ‚„ symmetry models. Models with different Aâ‚„ particle assignments are analysed for deviations from tribimaximal mixing. There are nine models presented in Chapter 5, with lepton doublets transforming as 3 (underlined) and right-handed charged leptons transforming as 1, 1', 1" (all underlined) ; five of these include right-handed neutrinos transforming as 3 (underlined) and make use of the seesaw mechanism. Chapter 6 contains the analysis of six models that assign all leptons to the 3 (underlined) representation, with four of these utilising the seesaw mechanism. The models are tested for any degree of fine tuning of the parameters that define the mass matrices. The effect of perturbations on the mixing angle observables, in particular sinÂ² âˆ…â‚ â‚ƒ and sinÂ² âˆ…â‚‚â‚ƒ, is studied, as well as the effect on the Jarlskog invariant, Jcp. Investigations of the (Mee)- âˆ‘Mv parameter space allow for comparison with current data, and can lead to the possible exclusion of a particular model by constraints from future data.
Keywords: Neutrinos -- Mass; Standard model (Nuclear physics); Particles (Nuclear physics)